NETWORK TOPOLOGY DESIGN ON THE TANGERANG IMMIGRATION POLYTHECNIC CAMPUS USING CISCO PACKET TRACER SIMULATOR - Rino Rahaditya Syahputra (Polteknik Imigrasi, 2019)
Government programs in developing technology are very important in realizing the availability of accurate, accountable data, increasing efficiency, security, and creating accountability for information technology services in implementing technology, especially the Ministry of Law and Human Rights so that strategic plans in implementing technology-based government systems The information aims to make the initial stages in the form of a simulation-based network topology design that will be made using the Cisco packet tracer simulator with the network concept on the Tangerang Immigration Polytechnic campus as an effort to facilitate the teaching and learning process and can produce immigration human resources who are fluent in implementing a government-based system. information Technology. The network topology design made using the Cisco packet tracer simulation application shows the results of a virtual, connected design that can then be implemented in the construction of a real network construction.